(untitled) (International Journal of Physiotherapy, 2020)
Background: Cervical disc herniation is one of the major conditions resulting in neck pain, which in turn affects the patient’s activities of daily living. The Conservative approach is always being challenging among these patients due to the feeling of insecurity and the related severity of symptoms. McKenzie’s approach has been used worldwide for slipped disc issues in providing relief by reducing the disc pressure and radiating symptoms. Deep Cervical Flexors strengthening plays a vital role in providing neck stability and thereby improving the posture. Case Summary: A case of neck pain with radiation into the left upper extremity going down to the left hand in a 47-year-old female was presented to physical therapy and has been referred by an orthopedic surgeon with a diagnosis of acute cervical disc prolapse at the C5-6 level. After the initial evaluation, muscle energy techniques were initially given to increase the ROM of the cervical spine as the neck was stiff. Mckenzie techniques were executed, including manual traction for 15 days along with basic ROM, neck isometrics, and DCF strengthening. Outcome measures: Numeric Pain Rating Scale (NPRS), Cervical ROM, Neck Disability Index (NDI), Tampa Scale for Kinesiophobia (TSK) were used. Conclusion: Mckenzie protocols combined with Muscle Energy Techniques (MET) and DCF strengthening exercises revealed that there was a significant improvement in the patient’s functional ADL with a marked reduction in disc herniation and its associated symptoms.